Background note on food environment: Prepared for the CGIAR A4NH Consultative Food Environment Workshop, Nov 5-7, 2019 - Nodari, Giulia Rota; Kennedy, Gina; Herforth, Anna; Downs, Shauna; Brouwer, Inge D. (CGIAR Research Program on Agriculture for Nutrition and Health, 2019)
The food environment represents the “range of foods that can be accessed in the context where people live and can enable or restrict healthy dietary choices” (FAO, 2016). According to the Committee on World Food Security’s High Level Panel of Experts (HLPE), food environments are considered healthy when they “enable consumers to make nutritious food choices with the potential to improve diets and reduce the burden of malnutrition” (HLPE, 2017). Therefore, working toward making food environments enablers of healthy food choices offers an untapped opportunity to positively impact diet quality and nutrition (FAO, 2016; Global Panel, 2017).